Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan lil Aalamin melalui Pembelajaran Projek Kearifan Lokal di Madrasah Ibtidaiyah - Martanti, Fitria; Fatkhuronji, Moch; Maskur, Maskur (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
This study aims to describe the implementation of learning projects with the theme of local wisdom in strengthening the profile of Pancasila students and the profile of Rahmatan lil Aalamin students. The location of the research was carried out in Madrasah Ibtidaiyah Taufiqiyah Semarang, which has implemented the Merdeka curriculum independently. This qualitative research uses instruments in the form of interviews, documentation, and observation. Data analysis used is data reduction, data presentation, and data verification. The results showed that learning local wisdom theme projects had been carried out optimally in Madrasah Ibtidaiyah Taufiqiyah Semarang. The dimensions of the Pancasila student profile that can be realized are faith, fear of God Almighty, noble morals, and working together. The student profile of Rahmatan lil Aalamin that can be realized is a civilization with shaleh social sub-values and tolerance values with collaborative sub-values. The driving factor for the implementation of local wisdom-themed projects is the understanding of teachers and project teams also parental support. The inhibiting factors are the completeness of supporting facilities, infrastructure, and limited land.